2016
DOI: 10.5586/am.1069
|View full text |Cite
|
Sign up to set email alerts
|

Biology, cultivation, and medicinal functions of the mushroom Hericium erinaceum

Abstract: <em>Hericium erinaceum</em> (Bull.: Fr.) Pers. is an edible fungus of great significance in medicine. It is rarely found in Europe, in contrast, it is common in Japan and North America. Its fruitbodies have been well-known for hundreds of years in traditional Chinese medicine and cuisine. A cradle of <em>H. erinaceum</em> cultivation is Asia. In Eastern Europe is rare in natural habitats, but can be successfully cultivated. Both fruitbodies and mycelia are rich in active, health promoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 100 publications
1
17
0
1
Order By: Relevance
“…Production of mycelium occurs over the wide range of temperature. Numerous studies have found an optimum temperature for growths of Basidiomycota between 20 and 30°C [22,23]. Obtained result is comparable with those of many kinds of mushrooms that exhibit relatively lowtemperature optima, ranging from 20 to 25°C in their submerged cultures [24].…”
Section: Optimization Of Culture Conditionssupporting
confidence: 64%
See 1 more Smart Citation
“…Production of mycelium occurs over the wide range of temperature. Numerous studies have found an optimum temperature for growths of Basidiomycota between 20 and 30°C [22,23]. Obtained result is comparable with those of many kinds of mushrooms that exhibit relatively lowtemperature optima, ranging from 20 to 25°C in their submerged cultures [24].…”
Section: Optimization Of Culture Conditionssupporting
confidence: 64%
“…2b). For the mycelium growth of different species of higher fungi, the optimal pH value ranges from 5.0 to 6.0, except for the arboreal species in which the optimal pH can be lowered down to 4.0 [23,25]. In our research, the highest amount of mycelium biomass of S. imbricatus was obtained at the initial medium pH = 6.…”
Section: Optimization Of Culture Conditionsmentioning
confidence: 53%
“…The methods of mushrooms cultivation described in this experiment were similar to that commonly used in commercial cultivation (Oei, 2003, Sokół et al, 2016.…”
Section: Experiments Designmentioning
confidence: 99%
“…H. erinaceus fruiting bodies and mycelia are known to produce several extensive bioactive compounds, including health promoting substances like γ-aminobutyric acid (GABA), ergothioneine, and lovastatin (Cohen et al, 2014) with different positive effects on the human body. As reported previously, various substances extracted from monkey head mushrooms have multiple pharmacological activities such as antimicrobial, anti-cancer (Gue et al, 2006), and antioxidant activities (Chyi et al, 2005), and can be used in the treatment of cancer, hepatic disorders, Alzheimer's and Parkinson's diseases, and wound healing (Sokół, 2015). In addition, H. erinaceus offers neuroprotective effects after ischemic brain injuries, peripheral nerve regenerative effects, and enhancement of sensory as well as functional recovery after nerve injury (Wong et al, 2012;Lee et al, 2014;Wong et al, 2015;Wong et al, 2016).…”
Section: Introductionmentioning
confidence: 87%